Analisis Miskonsepsi Peserta Didik Kelas XI MIA 1 SMA Negeri 7 Makassar Menggunakan Instrumen Test Diagnostik Two Tier (Studi pada Materi Pokok Asam – Basa) - Chairan, Khairul Ashar; Danial, Muhammad; Pratiwi, Diana Eka (Jurusan Kimia FMIPA UNM, 2021)
This research aimed to students misconceptions on the concepts of acids and bases. The research method used is descriptive quantitative method. The instrument used is a Two-Tier diagnostic instrument with a total of 20 items. Based on the results of research that has been done, the percentage of students 'conceptual understanding is 24.2%, students' misconceptions are 39.5%, do not understand the concept of students by 36.6%. Teachers and students are one of the causes of misconceptions in class XI MIA 1 of SMA Negeri 7 Makassar on the subject matter of Acid Basa. The process of assimilation of the concept of students is not successful, the low interest in learning of students, the teacher does not provide a detailed explanation of the concept, the teacher only uses conventional learning models (lectures) ,. Based on the data and causes of misconceptions above, it can be concluded that students in class XI MIA 1 Makassar 7 State High School experienced misconceptions on the concept of acids and bases.